MicroRNA-125a-3p affects smooth muscle cell function in vascular stenosis. (November 2019) - Hu, Wei; Chang, Guangqi; Zhang, Mao; Li, Yuxi; Yin, Lepin; Huang, Youjin; Feng, Chao; Gu, Yi; Wen, Dacui; Wang, Shenming
Abstract: Aims: Many studies have indicated that microRNAs are closely related to the process of peripheral arterial disease (PAD). Previously, we found that microRNA-125a-3p (miR-125a-3p) in restenotic arteries after interventional therapy of lower extremity vessels was notably decreased compared with that of normal control arteries. However, its role in the development of vascular stenosis is not yet clearly understood. The purpose of this study was to investigate the expression, regulatory mechanism and function of miR-125a-3p in the process of vascular stenosis. Methods and results: Quantitative reverse-transcription polymerase chain reaction assays indicated that miR-125a-3p in restenotic arteries after interventional therapy was significantly lower than that in normal control arteries. Immunofluorescence and in situ hybridization co-staining assays in arterial sections demonstrated that miR-125a-3p was mainly expressed in the medial smooth muscle layer. Transfection of miR-125a-3p mimics into cultured vascular smooth muscle cells (VSMCs) effectively inhibited cell proliferation and migration. Then, western blot and luciferase activity assays showed that recombinant human mitogen-activated protein kinase 1 (MAPK1) was a functional target of miR-125a-3p and was involved in miR-125a-3p-mediated cell effects. Finally, the lentiviral infection of miR-125a-3p in balloon-injured rat carotid vascular walls showed that miR-125a-3p overexpression significantly reduced the probability of neointimal membrane production. Conclusions: miR-125a-3p can effectively inhibit the function of VSMCs and the occurrence of vascular stenosis by targeting MAPK1. This study introduces a new molecular mechanism of PAD. We show that regulation of the miR-125a-3p level has the potential to provide a new treatment for PAD and other proliferative vascular diseases. Highlights: This study is the first to investigate miR-125a-3p in the cardiovascular system. The results indicate that miR-125a-3p can inhibit VSMC proliferation and migration by targeting MAPK1. In the rat carotid balloon injury model, exogenous miR-125a-3p effectively inhibited the proliferation of VSMCs and the formation of neointima. This new method of regulating miR-125a-3p levels by exogenous miR-125a-3p can effectively broaden the field of miRNA and small molecule therapy research and can provide clinicians with a significant probability of improving the treatment of cardiovascular diseases.